Medicinal benefits, biological, and nanoencapsulation functions of riboflavin with its toxicity profile: a narrative review - Lee, Tze Yan; Farah, Nuratiqah; Chin, Voon Kin; Lim, Chee Woei; Chong, Pei Pei; Basir, Rusliza; Lim, Wai Feng; Loo, Yan Shan (Elsevier BV, 2023)
Riboflavin is a precursor of the essential coenzymes flavin mononucleotide and flavin adenine dinucleotide. Both possess antioxidant properties and are involved in oxidation-reduction reactions, which have a significant impact on energy metabolism. Also, the coenzymes participate in metabolism of pyridoxine, niacin, folate, and iron. Humans must obtain riboflavin through their daily diet because of the lack of programmed enzymatic machineries for de novo riboflavin synthesis. Because of its physiological nature and fast elimination from the human body when in excess, riboflavin consumed is unlikely to induce any negative effects or develop toxicity in humans. The use of riboflavin in pharmaceutical and clinical contexts has been previously explored, including for preventing and treating oxidative stress and reperfusion oxidative damage, creating synergistic compounds to mitigate colorectal cancer, modulating blood pressure, improving diabetes mellitus comorbidities, as well as neuroprotective agents and potent photosensitizer in killing bloodborne pathogens. Thus, the goal of this review is to provide a comprehensive understanding of riboflavin's biological applications in medicine, key considerations of riboflavin safety and toxicity, and a brief overview on the nanoencapsulation of riboflavin for various functions including the treatment of a range of diseases, photodynamic therapy, and cellular imaging.